The kinetics of γ-H2AX during radiotherapy of head and neck cancer potentially allow for prediction of severe mucositis - Kazmierska Joanna; Barczak Wojciech; Winiecki Tomasz; Łuczewski Łukasz; Marciniak Magdalena; Suchorska Wiktoria (Radiology and Oncology, 2020)
The aim of the study was to evaluate the changes in γ-H2AX expression in peripheral blood lymphocytes (PBL) according to severity of radiation-induced mucositis.